Evaluation Quality Management System of Construction Management Consultants in Infrastructure Project Supervision A Poultry Factory in West Java - Alde Noverli. Y; Fitri Suryani; Dwi Dinariana (Journal of Comprehensive Science, 2026)
This study aims to analyze the implementation of the Quality Management System (QMS) based on ISO 9001:2015 by construction management consultants in supervising infrastructure projects at a poultry company in West Java, Indonesia, namely PT Bounty Segar Indonesia. The main focus is to identify factors influencing the effectiveness of QMS implementation, assess supervision effectiveness, and evaluate performance using an effectiveness ratio approach (e = D/A). The research employs a quantitative method using data collected through questionnaires, field observations, and document analysis. Data were analyzed using validity and reliability tests, correlation analysis, multiple regression, and factor analysis with statistical software. Additionally, a fishbone analysis was applied to identify root causes affecting project quality supervision.The results indicate that the implementation of QMS plays a significant role in improving the consistency of project supervision. However, several inhibiting factors still exist, including human resource competency, working methods, materials, equipment, environmental conditions, and measurement systems. The effectiveness of supervision is strongly influenced by the balance between the number of detected nonconformities and the corrective actions taken.In conclusion, ISO 9001:2015 implementation contributes significantly to improving project supervision quality, but requires further strengthening in field implementation and data-based control systems to achieve optimal effectiveness.